High anorectal malformation with associated rectovaginal fistula and uterine didelphys. A known but rare association! - Abd. Aziz, Azian; M, Noor Ezmas (2013)
Learning Objective: To generate awareness although uterine didelphys is a known association in anorectal malformation, its presence is rare. Improvement in imaging modalities and techniques in suspicious cases has enabled clearer demonstration of this anomaly. Brief Content: Anorectal malformations comprise a wide spectrum of diseases and associated anomalies which involve the distal anus and rectum as well as the urinary and genital tracts that can affect boys and girls. It can contribute to high morbidity and mortality in children. The incidence of anorectal malformation has been reported to be approximately 1/5000 live births. Better imaging modalities and techniques leading to depiction of clearer anatomy have further refined the diagnosis which helps in the subsequent management. Although not many cases of anorectal malformation are seen in our institution, associated anomalies like rectovaginal or rectovesical fistulas are commonly observed. We are illustrating a case of imperforated anus with associated rectovaginal fistula and uterine didelphys that was encountered in a 9 year old girl with high anorectal malformation. Although uterine didelphys is a known association; its presence with anorectal malformation is rare and scarcely reported in the literature. The contrast study and MRI pelvis of this patient are illustrated. Keywords: anorectal malformation, imperforated anus, uterine didelphys